Design and fabrication of a multi touch screen desktop for multipurpose usage - Mohd Salleh, Mat Sahat (2012)
This thesis is regarding the final year project for a diploma student in Universiti Malaysia Pahang (UMP). The title is building Multi Touchscreen Desktop. The student needs to design and fabricate a Multi Touchscreen Desktop for multipurpose usage. It is to overcome the problems that arise when using normal computer which use too many space in a room. Normal computer also cannot receive too many input at a time which make it time consuming. The student needs to use various fabrication processes in the making of this project. All the skill had been taught in previous lab courses in UMP. Firstly, the work must be plan well so the work can be finished in time. A gantt chart is constructed in order to show the date and time for the specific work to be done. Moreover, a flow chart is also constructed to visualize the step-by-step process of making this project. Literature review is done early to give better understanding about what is multi touch screen. Lots of research is done whether using internet or other media. Then the student makes the sketches of the multi touch screen desktop. All the sketches undergo screening process and only 4 that pass the screening. The 4 sketches are then refined before final concept is selected using scoring process. The final concept is then turned into 3D drawing. The 3D drawings are generated using computer software. After the detail of the drawing is finished, the project is fabricated. All the process is mainly done in the fabrication lab of UMP. Starting from the measuring and marking process until the assembly process is done using the tools and equipment in the lab. Next the product is checked for any defect that comes from the fabrication process. Lastly the project is tested to make sure the multi touch screen desktop can function well. Therefore the project can be used although with some flaw that could not being resisted.